Three pillars of urbanization: Migration, aging, and growth - Theresa Grafeneder-Weissteiner; Klaus Prettner; Jens Südekum (Universität Hohenheim, Fakultät Wirtschafts- und Sozialwissenschaften, 2018)
Economic development in industrialized countries is characterized by rising per capita GDP, increasing life expectancy, and an ever larger share of the population living in cities. We explain this pattern within a regional innovation-driven economic growth model with labor mobility and a demographic structure of overlapping generations. The model shows that there is a natural tendency for core-periphery structures to emerge in modern knowledge-based economies.
urn:nbn:de:bsz:100-opus-14660
Keywords: J10; O30; O41; R23; 330; agglomeration; migration; innovation; growth; demography; urbanization; core-periphery structure; regional inequality